EUROPEAN EXPERIENCE OF STRATEGIC PLANNING FOR THE DEVELOPMENT OF TERRITORIAL COMMUNITIES (INNOVATIVE ECONOMY, 2023)
Honchar L.V., Yarovyi K.O., Babaian D.P. EUROPEAN EXPERIENCE OF STRATEGIC PLANNING FOR THE DEVELOPMENT OF TERRITORIAL COMMUNITIESPurpose. The aim of the article is to study of the best practices of the European experience of strategic planning to increase the competitiveness of domestic territorial communities.Methodology of research. The methodological basis of the study was scientific methods of cognition based on a systematic approach to solving the tasks. A number of general and special scientific research methods were used to achieve the set goal and obtain research results: dialectical; monographic (when processing scientific publications); system analysis (when studying the current state of development of territorial communities); abstract and logical (to substantiate the key characteristics of strategic planning for the development of territorial communities); complex analysis (when forming conclusions and proposals for solving tasks) and others.Findings. An analysis of the best practices of strategic planning of European countries was carried out. It was established that there is no universal model of development of territorial communities in European countries, the way of organizing decentralized power in each country is related to its history, political and managerial culture, economy and social experience. It has been established that the strategic approach in the management of European countries has recently become widespread and is used at all levels, from the national to the level of autonomous territorial communities.Peculiarities of strategic planning of territorial communities in Ukraine were studied and it was established that a comprehensive approach is the basis for the implementation of state regional policy.It is noted that this approach involves taking into account the features of each territory, in particular, spatial, ecological, social and economic. It was established that the decentralization of power and resources created new opportunities for the development of domestic UTCs. It has been established that a clear division of powers between the state and individual territorial and regional authorities is a fundamental requirement for effective governance. It is proposed for further planning of the strategy of development of domestic UTCs to involve the population in all stages of its development, implementation and monitoring of implementation, which will allow to create conditions for achieving the goals of social and economic development of UTCs in accordance with the perspective priorities of state policy and taking into account the wishes and vision of the public.Originality. There was further development of research on the issue of strategic planning of the development of territorial communities in European countries in order to increase the competitiveness of domestic local government agencies.Practical value. The obtained research results will help strengthen the competitiveness of territorial communities, stimulate their economic growth and improve the quality of life of the population.Key words: decentralization; competitiveness; strategic planning; social and economic development; local community.
Keywords: decentralization; competitiveness; strategic planning; social and economic development; local community